TEMPORAL DYNAMICS OF EUTROPHICATION LEVEL AND SEDIMENTATION RATE IN CORAL REEF AREA OF SPERMONDE AND SEMBILAN ISLANDS, SOUTH SULAWESI - Rani, Chair; Nessa, M Natsir; Faizal, Ahmad; Werorilangi, Shinta; Tahir, Akbar; Jompa, Jamaluddin (Jurnal Ilmu Kelautan SPERMONDE, 2018)
Spermonde and Sembilan Islands (Bone Bay) are the central distribution of coral reefs in South Sulawesi. These archipelagos are likely to be at risk from eutrophication and sedimentation from intensive agriculture and aquaculture activities, in particular through transport of nutrients and materials discharged to the river systems on the Sulawesi mainland. The aim of this study was to analyse the temporal dynamics of eutrophication levels and sedimentation rates on coral reefs area of Spermonde and Sembilan Islands. Nutrient concentration and sedimentation rate were collected at monthly intervals over 4 months, at six stations: three in the Spermonde Islands (Laiya, Kodingareng, and Samalona Islands), and three in the Sembilan Islands, Sinjai District (Batanglampe, Kambuno, and Burungloe Islands), with two data collection points/replicates at each station/island. The results showed that phosphate concentration and sedimentation rates were higher in the Sembilan Islands, whereas nitrate concentrations were similar in both island groups. Nitrate concentration data indicated that eutrophication levels was varied, ranging from oligotrophic to eutrophic conditions, depends on months. In July and September, eutrophication was observed at all stations in both locations. Sedimentation rates were higher in the Sembilan Islands, but declined gradually until the end of the study time. Conversely, at stations in the Spermonde Islands, especially Samalona and Kodingarengkeke Islands, sedimentation level was increased significantly until the end of the study.